Cambios en el sistema de asentamientos rurales: la provincia de Teruel - Frutos Mejías, Luisa María; Solans Castro, Manuela; Chueca Diago, María Carmen (Geographicalia, 2017)
A number of studies have revealed how socioeconomical and technical changes during the 20th century have lead to a generalized emigration in the rural areas. This proccess has been particularly fast and acute in Spain, although it has not been homogeneous. The province of Teruel is a very representative example since it still has a high index of rurality, and between 1900 and 1981 it has lost almost half of its population. The aim of this paper is to show that this depopulation has amodified the system of settlements in a way depending to a great extent on the size of the former settlements and the number of isolaled farms, so causing a greater unbalance and spatial concentration of the population.